Creative Writing Without the Pain of Grammar: A Sourcebook for CW 10 - Eusebio-Abad, Heidi Emily (Journal of English Studies and Comparative Literature, 2007)
The moment I was asked to submit a proposal for the General Education (G.E.) Professorial Chair Award that I got in 2005, I already knew what I wanted to work on. For a tentative title, I wrote down, “Addressing Grammar and Composition Problems in a G.E. Creative Writing Class.” It was my first semester to teach the fairly new Revitalized General Education Program (RGEP) course of CW 10, the course on Creative Writing for Beginners. Teaching this course would prove to be a challenge since it could be taken by anyone at anytime, without the prerequisites of an English grammar or composition class. This sourcebook integrates brief discussions of grammar points and composition guides with the creative writing exercises. The coverage of the book generally follows the topics in the syllabus for CW 10. The format for presenting each lesson is composed of four sections: 1) some background or helpful information on the craft of writing, 2) a warm-up activity in the form of a suggested journal entry, of a ten-minute seatwork, or of a group activity, 3) a creative writing exercise to be done and submitted individually, and 4) some language or grammar trivia. Each lesson may be either introduced by or followed-up with a reading selection that models the writing technique, literary element, or genre in focus.